Spin cycle : how the White House and the media manipulate the news - Kurtz, Howard, 1953- (New York : Simon & Schuster, 1998)
Spin Cycle is the first behind-the-scenes account of the White House political operation as it packages and shapes the news by manipulating, misleading, and in some cases, intimidating the press. It is also the tale of how some of the nation's top journalists buy into these efforts and, often, put their own spin on the news. Compelling, infuriating, often devastatingly funny, this is the story you should read before you pick up the newspaper tomorrow morning.
The gaggle -- The master of spin -- In the dungeon -- First blood -- The seeds of paranoia -- The laundromat -- Breaking through the static -- Hezbollah -- Mister Clean -- Dribs and drabs -- Purely personal -- Hardball -- The frontiers of spin -- Charm offensive -- Toughing it out -- Dodging the bullet -- That woman.
'Revised and updated with a new epilogue from the author'--Cover.
'A Touchstone book.'
Includes bibliographical references: pages 328-332 and index.
Keywords: Clinton, Bill, -- 1946-; Press and propaganda -- United States -- History -- 20th century; Propaganda, American -- History -- 20th century; United States -- Politics and government -- 1993-2001.